Designing robust distributed average tracking (DAT) algorithms for multi-reference-signals produced by lipschitz-type dynamics - Yu Zhao; Yongfang Liu; Guanghui Wen (IWCSN 2017 : the 14th International Workshop on Complex Systems and Networks : December 8-10, 2017, Doha, Qatar, 2017)
This article designs a DAT algorithm for multi-reference-signals produced by multiple Lipschitz-type dynamics. There is a nonlinear term in the reference signals' dynamics which satisfies the Lipschitz-type condition. Based on state-dependent-gain designing approaches, a class of robust distributed average tracking algorithm is designed without requiring the same initial condition. The agent can track the AVG of the multi-reference-signals. A numerical simulation is shown finally.